(RE)EXAMINING POLITENESS CONCEPTS AND CONTENTIONS: IMPLICATIONS ON FILIPINO BRAND OF POLITENESS - Rafael Ibe Santos (Sanata Dharma University, 2022)
Efforts have been made to characterize the Philippine brand of linguistic politeness but literature on the subject (including language power) remains scarce. In response, this paper (re)examines key concepts and contentions in politeness theory and attempts to draw pertinent conclusions in the way politeness in language is demonstrated in Filipino context. Discourse on politeness, spanning from its infancy (from Gricean maxims and Lakoff’s politeness rules with references to Goffman’s face) to its blossoming years courtesy of Brown and Levinson is revisited as well as the ensuing arguments on the subject. Some implications particularly the universalness claims regarding politeness, as it is juxtaposed with Filipino politeness, are then drawn. A significant observation is that local experiences and practices contradict the universalness claim of western type of politeness. Uncovered are novel vistas on Filipino politeness as reflected in day-to-day and workplace situations. Finally, ingrained in the Filipino is a self-centered, multifaceted brand of politeness that is both face-saving and designed toward achieving material or non-material gain such as work security.